Which is more stable and specific: DSM‐5 internet gaming disorder or ICD‐11 gaming disorder? A longitudinal study. Issue 4 (9th February 2023) - Hong, Yu Na; Hwang, Hyunchan; Starcevic, Vladan; Choi, Tae Young; Kim, Tae Ho; Han, Doug Hyun
Abstract : Aim: The high comorbidity rates of internet gaming disorder (IGD) and gaming disorder (GD) with other psychiatric disorders are concerning. A follow‐up study of gamers from clinical and nonclinical samples with and without diagnoses of IGD or GD was conducted to investigate the changes in diagnoses over a 1‐year period, compare their diagnostic stability, and examine the patterns of co‐occurrence between IGD and GD with other psychiatric disorders over the same period. Methods: Baseline and 1‐year follow‐up data of 279 participants, including 120 problematic gaming patients and 159 gamers from the general population, were analyzed. Information on demographics, gaming habits, and self‐reported psychological status was collected. Additionally, a structured interview was conducted using the Gaming Diagnostic Interview and the Mini‐International Neuropsychiatric Interview. Results: Although there was no significant difference between the changes in IGD/GD diagnosis during the 1‐year period, 34.7% of the participants had a change in IGD diagnosis, while the number of GD cases increased to 60.4%. When evaluating the fixed effects of comorbidity on IGD and GD, attention‐deficit/hyperactivity disorder had the highest odds ratio for both IGD (75.23; 95% confidence interval [CI], 10.67–530.61) and GD (117.02 × 10 6 ; 95% CI, 2.23 × 10 6 –6132.64 × 10 6 ). Conclusion: These results reveal that a GD diagnosis might be more prone to change than an IGD diagnosis. GD was also found to be more affected by comorbid psychiatric disorders.